Strategi Partai Kebangkitan Bangsa (PKB) dalam Mendongkrak Perolehan Suara Pemilu 2019 di Kabupaten Pati - Addiansyah, Nur Rofiq; Setiyana, Ita; Mukhsinatulluaili, Mukhsinatulluaili; Ajaba, Mochammad Ariq; Vitta Ningsih, Sri Lestari (State Islamic Institute of Kudus (IAIN Kudus), 2021)
This paper will discuss how the existence of the National Awakening Party (PKB) in the 2019 election votes in Pati Regency. How the PKB vote got in the 2019 election in Pati, the existence of PKB in Pati, how PKB maintains its existence, will be discussed in this paper. The National Awakening Party (PKB) which is a pseudo-religious party born from NU led by Abdul Rahman Wahid, and declared on July 23, 1998 in Jakarta in the 2019 simultaneous elections in Pati Regency, was able to score six seats. The research method in this paper uses a qualitative research method with a case study type that is descriptive and tends to use analysis. While the technical data collection by studying documentation from books, journals, internet and other relevant sources to obtain secondary data. From the analysis using Pedersan's view with the theory of political party growth, PKB itself to get six seats in the 2019 simultaneous elections in Pati Regency was previously formed through several phases, the first is declaration, the second is authorization, the third is representation, and the last is relevance. There are several ways in which PKB maintains its existence itself, the first is by maintaining party solidarity. The second way is with strong support from the socio-religious organization Nahdlatul Ulama (NU). The third way is by the appearance of popular figures. And the last way is by having